Framing Pemberitaan Atlet Voli Megawati Hangestri di Liga Voli Korea pada Media bola.com dan okezone.com - Carissa Emilyana Wati; Sumardjijati Sumardjijati (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
Sports news today is increasingly being looked at by the public, unfortunately the presentation of news is not entirely paying attention to the objective and value aspects of the news, especially the view of the value of women in the news about female athletes who are often considered less proportional and cause other views that are not true. Using the constructivism paradigm to find out how athlete Megawati Hangestri was framed through the online media Bola.com and Okezone.com during her match in the 2024 Korean Volleyball League with 8-9 news stories each to study, using the framing analysis developed by Zhongdang Pan and Gerald M. Kosicki classifying framing devices into four main elements, namely syntactic structure, script structure, thematic structure, and rhetorical structure. The results found that Bola.com online media framed Megawati Hangestri as a professional athlete and hero in the eyes of the Indonesian people. Meanwhile, Okezone.com framed Megawati Hangestri as an inspirational influencer. Both produce positive narratives by accentuating Megawati Hangestri's achievements so as to form a positive image and be able to change public perceptions.